2019
DOI: 10.1111/wej.12506
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of iron nanoparticles infused polyethersulphone (Fe‐NPs/PES) membrane during treatment of BTEX‐contaminated wastewater

Abstract: In this study, polyethersulfone (PES) was infused with iron nanoparticles (Fe-NPs) obtained from the leaf of pomegranate plant to enhance hydrophilicity of the PES membrane. The resulted nanocomposite Fe-NPs/PES membrane obtained via phase inversion was characterized using a scanning electron microscope (SEM) for the morphology; a texture analyzer for the mechanical strength; an atomic force microscope (AFM) for the surface roughness; and water contact angle measurement for the degree of hydrophilicity. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(56 reference statements)
2
3
0
Order By: Relevance
“…The decrease in the contact angle reveals the enhancement of the hydrophilic property of PSF membrane. This is in agreement with the study reported by Unuigbe et al [ 34 ]. In addition, this observation corroborate the trend observed with the surface roughness of these membranes.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The decrease in the contact angle reveals the enhancement of the hydrophilic property of PSF membrane. This is in agreement with the study reported by Unuigbe et al [ 34 ]. In addition, this observation corroborate the trend observed with the surface roughness of these membranes.…”
Section: Resultssupporting
confidence: 94%
“…Figure 4 c,d depict the surface view and the cross-sectional view of PSF embedded with 10 wt.% HSOD, respectively. The surface view shows fewer pores which are smaller in comparison with those of the pure PSF membrane, attributable to the suppression of micro-void formation at high percentage loading of nanoparticles within the polymer matrix [ 34 ]. The typical thread ball-like shape of the HSOD particles are visible in the cross-section of the PSF membrane.…”
Section: Resultsmentioning
confidence: 99%
“…A similar observation was reported by Alruwaili et al [41]. This could be a result of the dominance of micro-void creation when nanoparticles embedded in the polymer matrix have been significantly increased [42]. The membrane becomes denser at a higher concentration of nanoparticles, which corroborates the results of Mukherjee and De [43].…”
Section: Surface Morphologies Of Fabricated Membranessupporting
confidence: 89%
“…Among these techniques, the pressure‐driven membrane technique has been proposed as an alternative process for the separation of textile wastewater because of its advantages, such as reduced energy consumption, low space requirements, low cost, high efficiency and environmental friendliness (Balta et al ., 2016; Unuigbe et al ., 2019; Wang et al ., 2019; Khan Mohammadi et al ., 2020). In recent years, wastewater separation using nanostructured hybrid membranes that operate via size exclusion and electrostatic interactions has attracted increasing attention from researchers in the water industry and scientific community for the separation of synthetic dyes from industrial effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous physicochemical techniques have been applied to remove dye-containing wastewater, such as impaction, precipitation, interception, solicitation, adhesion, physical and chemical adsorption, biological growth, flocculation and pressure-driven membrane separation methods (Chinoune et al, 2016;Bayat et al, 2018;Beluci et al, 2019;Duo et al, 2019;Song et al, 2019;Feng et al, 2020;Zheng et al, 2020). Among these techniques, the pressure-driven membrane technique has been proposed as an alternative process for the separation of textile wastewater because of its advantages, such as reduced energy consumption, low space requirements, low cost, high efficiency and environmental friendliness (Balta et al, 2016;Unuigbe et al, 2019;Wang et al, 2019;Khan Mohammadi et al, 2020). In recent years, wastewater separation using nanostructured hybrid membranes that operate via size exclusion and electrostatic interactions has attracted increasing attention from researchers in the water industry and scientific community for the separation of synthetic dyes from industrial effluents.…”
Section: Introductionmentioning
confidence: 99%